Structural and NBO Studies of Anomeric Effects in Polyoxa, Polyaza and Polycyclics Compounds - HAMZEHLOOIAN, MAHSHID; YEGANEGI, SAEED (Asian Journal of Chemistry, 2010)
The geometries of four hetrocyclic (polyaza polyoxa polycyclic) compounds have been completely optimized at B3lyp/6-31G** and HF/6-31G* ab initio quantum mechanical levels and compared with the X-ray structural data. Natural bond orbital (NBO) analysis has carried out quantitatively to estimate delocalization in O-C-N units. The optimized geometrical parameters agree with the acceptor-donor interaction scheme of NBO analysis. The results show that the structures of considered compounds affected by the anomeric effect.